In-loop oxygen reduction in HLM thermal-hydraulic facility NACIE-UP. (May 2018) - Bassini, S.; Di Piazza, I.; Antonelli, A.; Angelucci, M.; Sermenghi, V.; Polazzi, G.; Tarantino, M.
Abstract: NACIE-UP loop located at the ENEA Brasimone Research Centre is an experimental thermal-hydraulic facility working with liquid lead-bismuth eutectic (LBE). The facility was designed and constructed with the purpose to support the research activity on future nuclear reactors cooled by HLMs (Heavy Liquid Metals). A major problem in the operation of experimental HLM facilities concerns the chemical control of the coolant and, in particular, of the dissolved oxygen. Indeed, a reduction of the oxygen concentration in the HLM must be performed before each experimental thermal-hydraulic campaign in order to prevent the formation of PbO, whose deposition above piping and components may affect the experimental results. The present work describes the conditioning to low oxygen of the LBE inside NACIE-UP facility. The oxygen concentration reduction was performed by injecting Ar-3%H2 gas mixture in the riser column of the loop for 650 h and by varying the LBE temperature in the range 230–400 °C. The oxygen concentration in the LBE was monitored in the expansion vessel of the loop using a potentiometric Cu/Cu2 O oxygen sensor. The sensor showed that a deep oxygen reduction in the LBE was successfully obtained, even if the optimal working concentration for the operation of a HLM nuclear system was not achieved. The oxygen concentration was globally reduced from 10 −6 to 10 −12 % in weight at around 250 °C. Furthermore, the sensor revealed the establishment of M/Mx Oy equilibria in the expansion vessel, indicating that metal impurities dissolving from loop steel walls were here collected and influenced the electric potential of the sensor.